Production of albino slayer through a combination of crossing in brushmouth (Hypostomus plecostomus, Linnaeus 1758) ornamental fish - Ahmad Teduh; Dinar Tri Soelistyowati; Odang Carman; Harton Arfah (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2020)
The objectives of this research was to evaluate the inheritance of albino slayer phenotype in brushmouth (Hypostomus plecostomus, Linn 1758) through the crosses and reproduction performance. The crossing scheme consisted of reciprocal crosses between albino slayer and albino non slayer (SN, NS) and between albino slayer (SS), each spawning in pairs (1:1) with three replications and twice spawning. The fish used in this study were brushmouth fish (Hypostomus sp.) albino Slayer males 9.07 ± 0.5 cm, albino slayer females 8.96 ± 0.4 cm, albino non slayer males 8.87 ± 0.17 cm, and albino non slayer female 8.86 ± 0.16 cm. Slayer phenotype category was identified based on the caudal length fin with 4.43 ± 0.64 cm. Parameters determined included the phenotype distribution of albino slayer, total number of eggs, fertilization rate, hatching rate and survival rate. The results showed that all crossing schemes produced four phenotypes classes including normal slayer, normal non slayer, albino slayer and albino non slayer. The slayer phenotype of albino brushmouth was highest percentage (75%) in crossing with male albino slayer (SN, SS) and highest number of eggs, while the reciprocal crossing with female albino slayer (NS) produced albino slayer 55% and lower egg count. The ratio of tail fin length to body length in albino slayer phenotype was lower than normal phenotype of broom fish. The fertilization and hatching rates were not significantly different in all crosses; however the number of eggs decreased in the second spawning. The similar phenotype cross between albino slayer phenotypes (SS) resulted the best average of survival rate (92%). Abstrak Muncar merupakan salah satu sentra produksi hiu di Pulau Jawa dengan daerah tangkapan di perairan Selat Bali dan sekitarnya. Pendataan secara rutin terhadap hasil tangkapan hiu dan pari dilakukan sejak Bulan Mei 2018 hingga April 2019 di Pasar Ikan Brak dan Pelabuhan Perikanan Pantai (PPP) Muncar, Banyuwangi untuk mengetahui kom-posisi spesies dan distribusi ukuran hiu dan pari yang tertangkap dari perairan Selat Bali dan sekitarnya. Pengumpulan data dilakukan secara sensus dan hampir seluruh individu diidentifikasi sampai tingkat spesies serta diukur. Tercatat 3.551 individu hiu dan pari yang didaratkan di wilayah tersebut selama kurun waktu penelitian, yang terdiri atas 75 spesies dan 25 famili (49 spesies hiu dan 26 spesies pari). Spesies hiu yang paling umum ditangkap berasal dari famili Carcharhinidae, sedangkan kelompok pari didominasi oleh famili Dasyatidae. Tercatat ada 13 spesies hiu dan pari Apendiks II CITES yang ditangkap oleh nelayan Muncar, yaitu Carcharhinus falciformis, Alopias pelagicus, A. superciliosus, Isurus oxyrinchus, I. paucus, Sphyrna lewini, S. zygaena, Mobula mobular, M. tarapacana, M. thrustoni, Glaucostegus typus, Rhynchobatus australiae dan Rhina ancylostoma. Sebagian besar hiu dan pari yang ditangkap nelayan berada pada ukuran yuwana hingga remaja, yang belum matang kelamin atau sedang menuju dewasa.